Development of a Preemergent Nanoherbicide: From Efficiency Evaluation to the Assessment of Environmental Fate and Risks to Soil Microorganisms - Takeshita, Vanessa; Carvalho, Lucas Bragança [UNESP]; Galhardi, Juliana Aparecida [UNESP]; Munhoz-Garcia, Gustavo Vinícios; Pimpinato, Rodrigo Floriano; Oliveira, Halley Caixeta; Tornisielo, Valdemar Luiz; Fraceto, Leonardo Fernandes [UNESP] (American Chemical Society (ACS), 2022)
Nanoparticles based on biodegradable polymers have been shown to be excellent herbicide carriers, improving weed control and protecting the active ingredient in the crop fields. Metribuzin is often found in natural waters, which raises environmental concerns. Nanoencapsulation of this herbicide could be an alternative to reduce its losses to the environment and improve gains in its efficiency. However, there is a paucity of information about the behavior of nanoformulations of herbicides in environmental matrices. In this study, the stability of nanoencapsulated metribuzin in polymeric nanoparticles (nanoMTZ) was verified over time, as well as its dissipation in different soils, followed by the effects on soil enzymatic activity. The physiological parameters and control effects of nanoMTZ on Ipomoea grandifolia plants were investigated. No differences were verified in the half-life of nanoencapsulated metribuzin compared to a commercial formulation of the herbicide. Moreover, no suppressive effects on soil enzymatic activities were observed. The retention of nanoMTZ in the tested soils was lower compared to its commercial analogue. However, the mobility of nanoencapsulated metribuzin was not greatly increased, reflecting a low risk of groundwater contamination. Weed control was effective even at the lowest dose of nanoMTZ (48 g a.i. ha-1), which was consistent with the higher efficiency of nanoMTZ compared to the conventional herbicide in inhibiting PSII activity and decreasing pigment levels. Overall, we verified that nanoMTZ presented a low environmental risk, with increased weed control.
Keywords: biodegradation; chemical control; leaching; nanopesticide; soil enzyme activity; sorption-desorption